Knowledge, perception and attitude toward fibromyalgia among physical therapists in the United Arab Emirates: A cross-sectional study - Mona A. Almulla; Amna M. Farhani; Emad A. Aboelnasr; Fatma A. Hegazy (PLoS ONE, 2026)
Background Fibromyalgia (FM) is a chronic condition classified by widespread pain, fatigue, and associated symptoms. Patients with FM are frequently referred to physical therapists, whose knowledge of assessment criteria and management strategies is critical for timely recognition and effective care. Early diagnosis has been shown to improve outcomes, whereas delayed recognition often leads to prolonged suffering and increased healthcare costs. Aim The objective of this study was to examine the knowledge, perceptions, and attitudes of physical therapists in the United Arab Emirates (UAE) with respect to the diagnosis and management of FM. Methods A cross-sectional self-reported survey was distributed electronically to practicing physical therapists across the UAE. The survey collected demographic data, as well as information on confidence in determining and managing FM, awareness of international guidelines, perceptions of other healthcare providers roles, and knowledge of the risk factors. Results A total of 300 physical therapists were invited, and 240 completed the survey and met the inclusion criteria (response rate of 80%). The results revealed a predominantly female workforce, with 73.8% of participants identifying as female. The age of most respondents ranged between 23 and 42 years. Almost half of the participants had less than five years of experience. Nearly two-thirds of participants expressed confidence in diagnosing and managing FM cases. Most participants were unaware of any of the international FM practice guidelines (1990 ACR, 2010 ACR, 2012 Canadian). Conclusion The findings of this study underscore a concern for a lack of confidence and awareness among physical therapists in the UAE regarding the diagnosis and management of FM cases. Despite a significant proportion of participants reporting experience in managing FM cases, the majority were not familiar with recent FM practice guidelines, indicating potential gaps in knowledge and practice. This study highlights the importance of improving curricular integration of FM content, and greater dissemination of evidence-based guidelines. Addressing these gaps will be essential for promoting earlier diagnosis, reducing delays in management, and improving patient outcomes in the UAE.